Association Between Human Leukocyte Antigen-B*27 and Pathogenesis in Seronegative Spondyloarthropathies in Federation of Bosnia and Herzegovina - Elma FEJZIĆ; Izet EMINOVIĆ; Jasenko KARAMEHIĆ; Amela ŠAHOVIĆ; Sanela ŠIŠIĆ; Damir SULJEVIĆ (Archives of Rheumatology, 2019)
Objectives: This study aims to investigate the low-resolution human leukocyte antigen (HLA)-B locus polymorphisms between unrelated healthy individuals and patients with diagnosis of seronegative spondyloarthropathies and determine risky and protective allelic groups and genotypes. Patients and methods: The study included 104 healthy control individuals (52 males, 52 females; median age 43 years; range 2 to 76 years) and 96 patients (43 males, 53 females; median age 28.5 years; range 2 to 67 years) diagnosed with: ankylosing spondylitis (AS) (n=19), reactive arthritis (n=19), psoriatic arthritis (n=28) and undifferentiated spondyloarthropathies (n=30). Genomic deoxyribonucleic acid was extracted from peripheral blood to detect allelic groups of HLA class I and II. Single-specific-primer polymerase chain reaction was used for HLA genotyping and visualization of products after their separation on 1.5% agarose gel for horizontal gel electrophoresis. Results: Significantly increased frequency was found for HLA-A*02 and HLA-B*27 allelic variants in all groups of patients. The increased frequency of the HLA-B*35 allelic group in the control group represents the protective gene variant for the occurrence of AS. The predisposing genotype (HLA-B*27/B*44 and B*27/B*51) for the onset of disease was only found in AS patients. Conclusion: This study shows the strong association of HLA-B*27 antigen with spondyloarthropathies, which is considered a risk variant of the gene for the onset of disease. Protective and risky allelic variants and genotypes are rare and their detection as well as increased frequency are possible if larger numbers of patients are involved.